2020
DOI: 10.1177/1044389419889710
|View full text |Cite
|
Sign up to set email alerts
|

Photovoice as a Multilevel Tool for Gender and Sexual Identity Exploration

Abstract: Gender and sexual identity exploration (GSIE) consists of engaging in activities that allow an individual to discover their values, preferences, and boundaries related to gender and sexuality. Photovoice is a participatory research method that incorporates an intrapersonal, interpersonal, communal, and political approach to engaging with a given topic. The purpose of this article is to use existing research to illustrate how using photovoice method for GSIE does involve individuals in exploring gender and sexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…Previously, PhotoVoice has been used to explore identity meaning-making, health and humans service barriers faced by nonbinary young people [ 8 , 9 ], the experiences of LGBTQ young people formerly in foster care [ 65 ], and the experiences of LGBTQ college students [ 66 ]. Others have suggested that this methodology can be useful in gender and sexuality identity exploration [ 67 ], and Ingrey [ 68 ] goes as far as to describe photovoice as a genderqueer methodology for its ability to critically deconstruct gender and gendered spaces and pursue gender justice.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, PhotoVoice has been used to explore identity meaning-making, health and humans service barriers faced by nonbinary young people [ 8 , 9 ], the experiences of LGBTQ young people formerly in foster care [ 65 ], and the experiences of LGBTQ college students [ 66 ]. Others have suggested that this methodology can be useful in gender and sexuality identity exploration [ 67 ], and Ingrey [ 68 ] goes as far as to describe photovoice as a genderqueer methodology for its ability to critically deconstruct gender and gendered spaces and pursue gender justice.…”
Section: Methodsmentioning
confidence: 99%
“…Photovoice was determined to be an appropriate and suitable methodology because it has an established record of accomplishment in exploring the lived experiences of marginalized populations (Budig et al, 2018). For example, Photovoice can be seen when exploring topics such as Ethnicity (Miranda et al, 2021), Race (Davis & Mitchell, 2021;Vaishnav, 2021;Willett et al, 2021), Gender Identity (Christensen et al, 2020;Miranda et al, 2021), and Sexuality (Christensen et al, 2020;Bardhoshi et al, 2018;Capous-Desyllas & Mountz, 2019;Kessi, 2018;Wagner et al, 2016).…”
Section: Is Photovoice An Appropriate Approach For This Type Of Resea...mentioning
confidence: 99%
“…It reduces power differentials between researcher and participant [ 55 ], creating a “comfortable space for discussion” [ 56 ], and involving participants in a way that does not limit responses. Such advantages may be especially important for data collection with marginalized groups, such as SGMY [ 57 ]. By actively taking and selecting relevant photos for the interview, participants maintain agency over their participation in the research process.…”
Section: Introductionmentioning
confidence: 99%
“…By actively taking and selecting relevant photos for the interview, participants maintain agency over their participation in the research process. As a method, photo elicitation has been described as being capable of “empowering and emancipating participants by making their experiences visible” [ 57 ] and centering participant voices [ 58 ]. Photo elicitation interviews (PEIs), similar to semistructured interviews without visual cues, provide the researcher with an interview guide centering on relevant areas of interest, as well as the flexibility to allow for unexpected topics to emerge [ 59 ].…”
Section: Introductionmentioning
confidence: 99%